Confucian Ethics, Christian Ethics and the Principlist Approach in Biomedical Ethics - Lowe, Gee Y (中国基督教研究（ISSN：3068-479X）, 2025)
With the rapid advance in technology, the world is confronted with a new set of ethical challenges. China, in the height of her modernization project, certainly would feel the crunch of such onslaught. This paper examines Confucian ethics in light of a major, bioethical approach of the West.